Sistem Kendali Pengisian Jus Otomatis Menggunakan Sensor Infrared Dan Waterflow Berbasis PLC - Siti Afiyah Qatrunnada; Yurni Oktarina; Tresna Dewi; Evelina Ginting; Pola Risma (Journal of Applied Smart Electrical Network and Systems, 2020)
The need for automatic beverage vendors is quite high in public places and crowds, which will be more efficient and efficient than the beverage vendors who are human-friendly. This paper discusses the design of an automatic beverage vendor based on a programmable logic controller (PLC). The PLC used for this study is the production of Outseal, which has an Outseal Studio simulation program with a ladder diagram control. This automatic beverage vendor consists of input, process, and output. The primary input of this system is an infrared sensor, and a flow meter sensor to detect the cup's presence and how much juice poured to the cup. The DC motor and pump are the control output. A simulation program demonstrates the effectiveness of this automatic beverage supplier with the Outseal studio.